Flexible loop-closing scheme for distribution network based on cascaded power electronic transformer with multiple-AC-ports - LI Qian; ZHAO Junyu; WANG Shengnan; XIE Sizhe; XU Yonghai; WEN Xian (Diance yu yibiao)
The research on uninterrupted loop-closing load transfer in distribution network is of great significance to ensure the high requirements for power quality and supply reliability in industrial production and residential electricity. At present, the loop-closing of the distribution network usually requires the use of additional devices, which has problems such as poor economic efficiency. In recent years, the research on power electronic transformers based on multiple-AC-ports has gradually attracted attention and has been put into practical application. For this application scenario and the demand for uninterrupted loop-closing load transfer, flexible loop-closing can be achieved based on the control of different ports of power electronic transformers to expand its application functions. This paper proposes an AC flexible loop-closing scheme based on the multiple-AC-ports cascaded H-bridge type power electronic transformer (MAC-CHB-PET). The structure of MAC-CHB-PET is analyzed. The internal mechanism of the impulse current and steady-state current generated during loop-closing are analyzed, and a power command value calculation method based on MAC-CHB-PET loop-closing regulation is proposed based on the selected characteristic factors. Furthermore, the AC flexible loop-closing scheme for uninterrupted load transfer is proposed, based on MAC-CHB-PET, which adopts coordinated control of active and reactive power at two AC ports to regulate the AC bus voltage and achieve AC flexible loop-closing. A simulation model is established to verify the feasibility of the proposed AC flexible loop-closing scheme.